Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.4 - Adding and Subtracting Rational Expressions with Different Denominators - Exercise Set - Page 516: 50



Work Step by Step

$\frac{-1}{a-2}$+$\frac{4}{4-2a}$= $\frac{-1}{a-2}$+$\frac{4}{2(2-a)}$= $\frac{2(-1)}{2(a-2)}$+$\frac{(-1)4}{(-1)(2)(2-a)}$= $\frac{-2}{2(a-2)}$-$\frac{4}{2(a-2)}$= $\frac{-2-4}{2(a-2)}$=$\frac{-6}{2(a-2)}$= $\frac{-3}{(a-2)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.